2017
DOI: 10.1002/cncr.30736
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 dose‐escalation study of mirvetuximab soravtansine (IMGN853), a folate receptor α‐targeting antibody‐drug conjugate, in patients with solid tumors

Abstract: IMGN853 demonstrated a manageable safety profile and encouraging preliminary clinical activity, particularly in patients with ovarian cancer. The results establish a recommended phase 2 dosing of 6.0 mg/kg (based on adjusted ideal body weight) once every 3 weeks. Cancer 2017. © 2017 American Cancer Society. Cancer 2017;123:3080-7. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 30 publications
4
73
0
Order By: Relevance
“…Importantly, the terminal half life determined at doses ≥1.0 mg/kg showed no dose dependence with respect to clearance or volume of distribution parameters. Cycle 3 exposure metrics indicated that there was no meaningful accumulation of mirvetuximab soravtansine after multiple doses [64].…”
Section: Antibody-drug Conjugatesmentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly, the terminal half life determined at doses ≥1.0 mg/kg showed no dose dependence with respect to clearance or volume of distribution parameters. Cycle 3 exposure metrics indicated that there was no meaningful accumulation of mirvetuximab soravtansine after multiple doses [64].…”
Section: Antibody-drug Conjugatesmentioning
confidence: 99%
“…on day 1 of a 21-day cycle (i.e., once every 3 weeks) to patients with FRα-positive solid tumors, which included individuals with ovarian, endometrial, cervical, renal and NSCLC [64]. A total of 44 patients were enrolled, with the first 30 receiving mirvetuximab soravtansine at escalating doses from 0.15 to 7.0 mg/kg calculated on total body weight.…”
Section: Antibody-drug Conjugatesmentioning
confidence: 99%
See 2 more Smart Citations
“…The first-in-human, Phase I study of single-agent mirvetuximab soravtansine in patients with EOC and other FRα-positive solid tumors established the recommended Phase II dose (RP2D) as 6.0 mg/kg, using adjusted ideal body weight (AIBW), administered once every 3 weeks [37]. The use of AIBW to calculate mirvetuximab soravtansine dosing was shown to reduce intracohort variability in pharmacokinetic exposure metrics.…”
Section: Background and Rationalementioning
confidence: 99%